Enhancing visitor learning and information access through Virtual Reality at the Museum Pendidikan Nasional - Hafsah Nugraha; Agus Rusmana; Ute Lies Siti Khadijah (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. Museum Pendidikan Nasional (Musdiknas) carries out activities that utilize websites and social media by showing virtual reality content in education in Indonesia to meet visitors' information needs. This research aims to examine virtual reality's potential in meeting museum visitors' information needs. Research Methods. Quantitative methods were used with students of the Universitas Pendidikan Indonesia who had accessed the Musdiknas virtual reality with a total of 316 people as participants. Data Analysis. Data from questionnaires, observations, and literature studies were used for descriptive data analysis. Results. Musdiknas virtual reality and social media have the characteristics of programmable participation, natural semantics, and constructivism to support efforts to meet visitors' information needs. Visitors use Musdiknas virtual reality as a learning tool to gain the experience and knowledge they need to meet their information needs. Conclusion. Musdiknas strives to continue developing its environment by utilizing virtual reality as a form of adaptation to technology, providing meaning and experience through exhibitions that are displayed and accessed remotely, thereby meeting the information needs of museum visitors. Further, researchers can measure the relationship and influence between variables and research the use of virtual reality at other museum locations.